1999
DOI: 10.1302/0301-620x.81b2.0810273
|View full text |Cite
|
Sign up to set email alerts
|

The prediction of failure of the stem in THR by measurement of early migration using EBRA-FCA

Abstract: We report the ten-year results for three designs of stem in 240 total hip replacements, for which subsidence had been measured on plain radiographs at regular intervals. Accurate migration patterns could be determined by the method of Einzel-BildRoentgen-Analyse-femoral component analysis (EBRA-FCA) for 158 hips (66%).Of these, 108 stems (68%) remained stable throughout, and five (3%) started to migrate after a median of 54 months. Initial migration of at least 1 mm was seen in 45 stems (29%) during the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
127
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(137 citation statements)
references
References 22 publications
7
127
0
3
Order By: Relevance
“…The additional radiation exposure required by a double examination is, in our view, not justified in this context. The ability of early migration measurements to predict later aseptic loosening has been established [5,13,16,19]. Marker-based RSA is considered the gold standard for measurement of implant migration, and it has been used as a standard of comparison for other radiographic methods, such as the Sutherland, Wetherell, and Sulzer methods or EBRA (Ein-Bild-Röntgen-Analyse, single-image roentgen analysis) [2,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The additional radiation exposure required by a double examination is, in our view, not justified in this context. The ability of early migration measurements to predict later aseptic loosening has been established [5,13,16,19]. Marker-based RSA is considered the gold standard for measurement of implant migration, and it has been used as a standard of comparison for other radiographic methods, such as the Sutherland, Wetherell, and Sulzer methods or EBRA (Ein-Bild-Röntgen-Analyse, single-image roentgen analysis) [2,6].…”
Section: Discussionmentioning
confidence: 99%
“…We tested interchangeability of the two methods in a clinical setting by a bounding criterion defined as the mean ± 2 standard deviations of the measured differences (bounding approximately 98% of all measured differences). The smallest clinically relevant magnitude of migration is difficult to define, and several clinical investigations that have related early migration to later aseptic loosening have used thresholds ranging from 1.2 to 2.6 mm [5,13,15,16,19]. We therefore chose a conservative value of clinically relevant migration of ± 0.5 mm or greater in magnitude, ie, much less than thresholds that have been used to predict later loosening.…”
Section: Methodsmentioning
confidence: 99%
“…EBRA-FCA has an accuracy of better than ± 1.5 mm (95% CI) when compared to RSA, a Cronbach alpha coefficient of 0.84 [3], a specificity of 100%, and sensitivity of 79% [3]. Using a cutoff value of 1.5 mm for femoral stem subsidence in the first 2 years, EBRA-FCA has a sensitivity of 69%, specificity of 80%, and accuracy of 79% in predicting implant failure [28].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Freeman and Plante-Bordeneuve [13] and Kobayashi et al [25] demonstrated the subsidence of a femoral stem at 2 years could predict failure at long-term followup. The association between early implant stability and long-term survivorship is well established for a variety of stem designs [23,28,38,43], with the gold standard in evaluating initial implant stability being radiostereometric analysis (RSA) [8,39]. Another validated technique to measure implant migration is Ein-Bild-Roentgen-Analysefemoral component analysis (EBRA-FCA) [3,27], which also allows accurate measurement of femoral stem subsidence without the need for tantalum markers [4] and can be performed retrospectively using standard pelvic radiographs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation